Plano de logística sustentável no Poder Judiciário: os impactos da implantação no Tribunal de Justiça do Estado do Pará (2016/2020) - Lima, Kelly Regina Lima de (2020)
The theme of public policies in the socio-environmental area in the Judiciary is increasingly present in meetings that seek the continuous improvement of the Brazilian justice system. The institution of Resolution of the National Council of Justice No. 201, of March 3, 2015, was the starting point for the Judiciary to adopt a Sustainable Logistics Plan, inserting it as an instrument linked to the strategic planning of the Courts. In this context, the Pará State Court of Justice (TJ/PA) implemented its first Sustainable Logistics Plan (PLS), with a five-year term (2016/2020), containing goals, indicators and deadlines. From this, a horizon of challenges was designed for the public managers responsible for the actions provided for in the thirteen sustainable plans established. Through bibliographic research, documentary analysis, semistructured interviews with the linked public managers, with an exploratory and descriptive focus and a qualitative approach, this research sought to investigate the impacts of the implementation of the first PLS of the TJ / PA, describing the diffusion of the sustainability agenda in the Judiciary, identifying the challenges and facilities encountered by managers and proposing actions to inhibit or reduce the difficulties encountered, in order to contribute to the construction of the new PLS to be implemented from 2021. With the analysis of the research data it was possible to conclude that the involvement of the Court's top management, better awareness of the staff on the theme of sustainability and the change of some work processes, are differentials of public management that leads to the construction of a sustainable court, where the administrators become the main agents of change.